Taxation and economic crisis in Spain - Ramos Llanos, Antonio Javier (Razón y fe, 2018)
In a situation of a serious economic and fiscal crisis affecting all European economies and especially the Spanish economy, this article presents possible alternative approaches about changes in taxation in our country. These alternatives can contribute, along with the readjustments in public spending, in reestablishing the balance of public finances, and can also facilitate the creation of favorable conditions to growth, creation of employment and the achievement of a fairer distribution of income and wealth.
Keywords: Spain; economic crisis; taxation; taxes; employment